PENGARUH KUALITAS LAYANAN TERHADAP NILAI PELANGGAN DAN KEPUASAN PELANGGAN RENTAL MOBIL FANY DI KOTA PALU - Rifai, Muhamad Rifai (Katalogis, 2016)
The objectives of this research are: 1) to know and analyze the effect of service quality on Customer Value,2) to know and analyze the effect of service quality on customer satisfaction. 3) to know and analyze the effect of Customer Value on customer satisfaction. This is an explanatory research to explain the relationships among investigated variables involving 180 customer of Fany Car Rental in Palu City that have been selected using purposive technique sampling. Based on the hypotheses testing using of Structural Equation Modeling (SEM), it concludes that: 1) service quality performs positive and significant effect on customer value;2) service quality performs positive and significant effect on customer satisfaction; 3) customer Value performs positive and significant effect on customer satisfaction.